Ammonia nitrogen stress damages the intestinal mucosal barrier of yellow catfish (Pelteobagrus fulvidraco) and induces intestinal inflammation - Liu, Senyue; Luo, Lin; Zuo, Fengyuan; Huang, Xiaoli; Zhong, Liang; Liu, Sha; Geng, Yi; Ou, Yangping; Chen, Defang; Cai, Wenlong; Deng, Yongqiang (Frontiers in Physiology, 2023)
Nitrogen from ammonia is one of the most common pollutants toxics to aquatic species in aquatic environment. The intestinal mucosa is one of the key mucosal defenses of aquatic species, and the accumulation of ammonia nitrogen in water environment will cause irreversible damage to intestinal function. In this study, histology, immunohistochemistry, ultrastructural pathology, enzyme activity analysis and qRT-PCR were performed to reveal the toxic effect of ammonia nitrogen stress on the intestine of Pelteobagrus fulvidraco. According to histological findings, ammonia nitrogen stress caused structural damage to the intestine and reduced the number of mucous cells. Enzyme activity analysis revealed that the activity of bactericidal substances (Lysozyme, alkaline phosphatase, and ACP) had decreased. The ultrastructure revealed sparse and shortened microvilli as well as badly degraded tight junctions. Immunohistochemistry for ZO-1 demonstrated an impaired intestinal mucosal barrier. Furthermore, qRT-PCR revealed that tight junction related genes (ZO-1, Occludin, Claudin-1) were downregulated, while the pore-forming protein Claudin-2 was upregulated. Furthermore, as ammonia nitrogen concentration grew, so did the positive signal of Zap-70 (T/NK cell) and the expression of inflammation-related genes (TNF, IL-1β, IL-8, IL-10). In light of the above findings, we conclude that ammonia nitrogen stress damages intestinal mucosal barrier of Pelteobagrus fulvidraco and induces intestinal inflammation.